Cells in the Non‐Uniform Magnetic World: How Cells Respond to High‐Gradient Magnetic Fields. (25th June 2018) - Zablotskii, Vitalii; Polyakova, Tatyana; Dejneka, Alexandr
Abstract : Imagine cells that live in a high‐gradient magnetic field (HGMF). Through what mechanisms do the cells sense a non‐uniform magnetic field and how such a field changes the cell fate? We show that magnetic forces generated by HGMFs can be comparable to intracellular forces and therefore may be capable of altering the functionality of an individual cell and tissues in unprecedented ways. We identify the cellular effectors of such fields and propose novel routes in cell biology predicting new biological effects such as magnetic control of cell‐to‐cell communication and vesicle transport, magnetic control of intracellular ROS levels, magnetically induced differentiation of stem cells, magnetically assisted cell division, or prevention of cells from dividing. On the basis of experimental facts and theoretical modeling we reveal timescales of cellular responses to high‐gradient magnetic fields and suggest an explicit dependence of the cell response time on the magnitude of the magnetic field gradient. Abstract : Cells in a non‐uniform magnetic field are subjected to magnetic gradient forces capable of altering different aspects of cell machinery: cytoskeleton organization, vesicle transport, intracellular ROS levels, apoptosis, differentiation pathways, division, etc. Intracellular targets of magnetic fields and timescales of cellular responses to high‐gradient magnetic fields are revealed.